2014
DOI: 10.1111/ijpo.244
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of repeated exposure and flavour–flavour learning as mechanisms to increase preschooler's vegetable intake and acceptance

Abstract: These results suggest a robust and persistent effect of repeated exposure but no effect of flavour-flavour learning. Offering pure vegetable tastes repeatedly is sufficient to increase intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…Seven papers included in this review explored the effectiveness of repeated exposure alone for increasing children’s liking and consumption of vegetables [21, 31, 35, 36, 38, 44, 45]. With this method, children are repeatedly offered and encouraged to try a target vegetable, with papers in this review testing 7 to 14 exposures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven papers included in this review explored the effectiveness of repeated exposure alone for increasing children’s liking and consumption of vegetables [21, 31, 35, 36, 38, 44, 45]. With this method, children are repeatedly offered and encouraged to try a target vegetable, with papers in this review testing 7 to 14 exposures.…”
Section: Resultsmentioning
confidence: 99%
“…Six of these papers tested the effectiveness of flavour-flavour learning to increase children’s consumption of vegetables [35, 36•, 37, 38, 41, 44]. While most of these studies found no advantage of flavour-flavour learning beyond that of repeated exposure [35, 37, 38, 44], one study [41] suggests that offering familiar and liked dips to children who are sensitive to bitter tastes may be useful for increasing consumption of brassicae (green, cruciferous vegetables) in the short term when served with dip. Further to this, the research suggests pairing bitter vegetables (Brussels sprouts) with cream cheese (with or without added sugar) for 14 days can significantly increase children’s rated liking of Brussels sprouts when subsequently presented plain, although this did not increase their consumption [36•].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall conclusion that emerges from this research is that repeated exposure is effective in increasing intake of vegetables in children, and that FFL and FNL offer no benefits beyond those found through the repeated exposure effect (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62) . Our study added to this knowledge by comparing two variants of a repeated exposure paradigm for its effectiveness to increase vegetable acceptance and intake.…”
Section: Behavioural Strategies To Increase Acceptance and Intakementioning
confidence: 82%
“…In addition, cognitive forms of learning can play a part in eating behaviour. However, children are not sensitive to health messages, which may even negatively affect their acceptance of foods (55) . When children are around 2 to 3 years old, they often develop an increased reluctance to try new foods (7,8) .…”
Section: Development Of Food Preferencesmentioning
confidence: 99%